Adapting Muhammadiyah’s Manhaj Tarjih for Public Policy Formulation: Triadic Policy Reasoning Model (TPRM) Based on Bayani, Burhani, and Irfani Epistemology - Ramliyanto (PT. Global Research Collaboration, 2026)
Public policy formulation in the 21st century is confronted with a paradox: the abundance of big data and empirical evidence does not necessarily guarantee the success and societal acceptance of a policy. This conceptual article examines the limitations of the Evidence-Informed Policy (EIP) paradigm, which has yet to fully integrate scientific evidence, legal legitimacy, and ethical considerations into a coherent reasoning framework. As an innovative solution, this article adapts Muhammadiyah's Manhaj Tarjih—which rests on the integration of Bayani, Burhani, and Irfani epistemologies—into state policy governance. Through a conceptual translation approach, this Islamic methodology is recontextualized into a secular-democratic public policy reasoning framework designated as the Triadic Policy Reasoning Model (TPRM). This model positions Bayani as constitutional normative legitimacy, Burhani as science-based empirical validity, and Irfani as ethical wisdom. The circular-spiral interaction of these three elements generates The Principle of Integrated Policy Reasoning, wherein policy quality is formulated as an integrative function of legality, rationality, and morality. This article provides an alternative theoretical foundation for public administration and demonstrates that Muhammadiyah's epistemological manhaj possesses universal relevance in realizing state decisions that are legitimate, effective, and equitable.